Pengembangan Multimedia Interaktif Gelombang Bunyi Berbasis PBL menggunakan Lumi untuk Peserta Didik Kelas XI SMA - Vebby Oksaviona; Nur Islami; Muhammad Nasir (Postgraduate, University of Mataram, 2023)
This study aims to describe the development, feasibility, and practicality of PBL-based sound wave interactive multimedia using Lumi. The research method used is research and development. The model used is an Instructional Design type ADDIE which consists of 5 stages namely Analyze, Design, Development, Implementation, and Evaluate. The results showed that PBL-based sound wave interactive multimedia using Lumi was declared feasible by the validator with an average Aiken validity index of 0.86 (very high). The teacher as a practitioner states that practical interactive multimedia is used in learning physics with an average value of 93.30 (very practical). Students also stated that practical interactive multimedia was used in learning physics with an average value of 90.46 (very practical). Based on the results of the study, it can be concluded that PBL-based interactive multimedia using Lumi is declared feasible and practical for use in the physics learning process, especially in sound wave material.